FACTOR ANALYSIS OF THE TOURISM SECTOR IN THE ADRIATIC-IONIAN INITIATIVE COUNTRIES - Ognjen Erić; Bojan Baškot; Dalibor Tomaš (Acta Economica, 2025)
Tourism represents a key segment of economic development in the countries of the Adriatic-Ionian Initiative (AII), contributing to the gross domestic product (GDP) and influencing employment, investments, and the trade balance of the region. This analysis examines the trends of tourism creation and diversion in eight AII countries-Albania, Bosnia and Herzegovina, Croatia, Greece, Italy, Montenegro, Serbia, and Slovenia-over the period from 1995 to 2024.This paper employs a multivariate approach to identify key factors that shape the competitiveness of destinations and contribute to the stability of the tourism sector. The study considers the impact of infrastructure investments, political stability, macroeconomic indicators, government policies on tourism subsidies, as well as the effects of pandemics and global economic crises on tourism flows.